Meg and her circus tricks - Percy, Graham (Mankato, Minn. : Child's World, 1991)
The tricks Meg learns at Uncle Zeb's circus stand her in good stead during a lull in her brother's birthday party.
Keywords: Circus -- Juvenile fiction; Elephants -- Juvenile fiction; Birthdays -- Juvenile fiction